FT-IR Study of Silk Fibroin/Polyaspartic Acid Scaffolds Prepared by Electrospinning - Qiao-Yan, Chen; Guang-Mei, Chen; Feng-Jun, Zhang; Rong, Li; Yi-Ping, Huang (Asian Journal of Chemistry, 2012)
Silk fibroin (SF)/polyaspartic acid (PASP) porous scaffolds were prepared by electro-spinning method with the aim to develop a new scaffold for tissue engineering. In the FT-IR spectra, with the addition of polyaspartic acid, the bands of silk fibroin had no obvious change. By the effects of electro-spinning, the bands of amide II and amide III of silk fibroin shifted to the lower wavenumber which meant the characteristic peaks of the silk II form, obviously, but the strong bands of amide I had no notable change. With the treatment of ethanol the structure of silk fibroin changed more completely and the bands of amide I shifted to the low wave number. The results indicated that there had no effect on silk fibroin’s structure when added polyaspartic acid in SF/PASP scaffolds. With the stretch of electro-spinning, the structure of SF/PASP scaffold changed owing to the polymer chains orientation. The silk I form changed to silk II form mostly by the ethanol treatment. The effects of the polyaspartic acid on the morphology of the porous scaffolds were investigated by SEM. The results provided that the addition of the polyaspartic acid had a good effect on electrospinning to make porous scaffolds.